Peirce: Re-Staging the Sign in the Work of Art - Morris, Sharon (Recherches sémiotiques / Semiotic Inquiry)

(untitled) (Association canadienne de sémiotique / Canadian Semiotic Association, 2013)
In the tradition of Rosalind Krauss’ essay “Notes on the Index” (1986) I want to re-posit the importance of the indexical status of the work of art and look at how Peirce’s views of aesthetics, his theory of the sign, and his version of phenomenology, can be useful to our understanding of contemporary works of art. The work of art that emerges from reading Peirce is not a representation of an object in the world but a mode of presentation of experience and in particular feeling. Defined as a complex form of icon, a hypoicon, the work of art is not constrained to mimetic representation but engaged in actively re-interpreting our world and our sense of self, cutting through preconceptions by returning us to the present : presentness, and the possibilities of firstness. Peirce’s late discussion on the study of phenomena, phaneroscopy, allows us to understand the work of art both as a part of our experience, and also as giving meaning to our experience : the work of art as a re-staging of the sign on the cusp between possibility and existence.